Descriptive characteristics and in‐hospital mortality of critically bleeding patients requiring massive transfusion: results from the Australian and New Zealand Massive Transfusion Registry. Issue 3 (8th February 2017) - Ruseckaite, R.; McQuilten, Z. K.; Oldroyd, J. C.; Richter, T. H.; Cameron, P. A.; Isbister, J. P.; Wood, E. M
Abstract : Background and Objectives: Critically bleeding patients requiring massive transfusion (MT) are clinically challenging, and limited data exist to support management decisions. This study describes patient characteristics, transfusion support and clinical outcomes from the Australian and New Zealand (NZ) Massive Transfusion Registry (ANZ‐MTR). Materials and Methods: Retrospective, cohort study of all adult patients receiving MT (≥5 units red blood cells [RBC] in 4 h) at participating ANZ‐MTR hospitals, 2011–2015. Mortality information was collected from the Australian National Death Index and NZ Ministry of Health. Associations between patient characteristics and outcomes were modelled using logistic regression. Results: A total of 3560 MT cases were identified. For in‐hospital deaths, cardiothoracic surgery was the most frequent bleeding context (24·5%) followed by trauma (18·3%). Age (OR = 1·03; 95% CI: 1·02–1·04), more comorbidities (OR = 1·14; 95% CI: 1·09–1·21), larger volume of RBC in first 24 h from MT onset (OR = 1·04; 95% CI: 1·02–1·06), higher platelet to RBC ratio at 4 h (OR = 2·76; 95% CI: 1·14–6·65) and higher activated partial thromboplastin time (OR = 1·02; 95% CI: 1·01–1·03) were associated with in‐hospital mortality. Conclusion: Patients with more comorbidities, older age, traumatic or surgical bleeding or requiring more blood components had higher in‐hospital mortality. These findings provide a basis to evaluate and monitor practice relating to optimal use of blood products, variation in transfusion practices and patient outcomes, and also enable benchmarking of hospital performance for management of MT in specific patient groups.